On Discontinuous Distribution of Bombay Duck Harpadon Nehereus (Ham 1822) - Mohammad Zafar Khan (Journal of Indian Fisheries Association, 2016)
Bombay duck, Harpadon nehereus (Ham.) is abundantly found on the northwest and northeast coasts of India. The discontinuous distribution of the species has been a subject of speculation without any appropriate theory or conclusive evidence. The present communication is an attempt towards finding an answer to this problem with respect to Zoo-geo-phenomenon which might have resulted in its discontinuous distribution.